Comparison of the complications of passive drainage and active suction drainage after pancreatectomy: A meta-analysis - Xinyang, Zhou; Taoying, Lei; Xuli, Lan; Jionghuang, Chen; Framing, Zhong (Frontiers in Surgery, 2023)
Objective This study aimed to compare the effect of passive drainage and active suction drainage on complications after pancreatectomy. Methods The Chinese and English databases were searched and covered in this study on the comparison of passive and active suction drainage after pancreatectomy from the database establishment to March 2020. A meta-analysis was conducted with the RevMan5.3 software. Results On the whole, 1903 cases were included in eight studies, including 994 cases in the passive drainage group, 909 in the active suction drainage group, 1224 in the pancreaticoduodenectomy group, as well as 679 in the distal pancreatectomy group. No statistically significant difference was identified between the two groups in the incidence of total complications, the rate of abdominal hemorrhage, the rate of abdominal effusion, the death rate and the length of stay after pancreatectomy (all P > 0.05), whereas the difference in the incidence of pancreatic fistula after distal pancreatectomy between the two groups was of statistical significance (OR=3.35, 95% CI= 1.12-10.07, P=0.03). No significant difference was reported in pancreatic fistula between the two groups after pancreaticoduodenectomy. Conclusion After distal pancreatectomy, active suction drainage might down-regulate the incidence of postoperative pancreatic fistula.